Transforming systems engineering principles into integrated project team practice - Arnold, S (Engineering Systems Department, 2008)
This investigation considers the composition, status, principles and defence acquisition setting of systems engineering. From these some opportunities for enhancement of its practice are considered. It opens with a re-assessment of the disciplinary essence of systems engineering. Systems engineering is considered as an amalgam of three components – systems reasoning, engineering and management – that form a coherent and distinctive discipline. It is advanced that a fresh balance of system-related factors, characterised in this text as systems reasoning, is the distinguishing essence of systems engineering. It conveys a rationale for present-day practice and provides a basis for advancements. Consideration is given to the construction of a systems engineering framework, built from a re-interpretation of engineering and management science constructs. A triptych of viewpoints of systems engineering, comprising connected representations of business process, organisational capability and individual competence, is proposed and outlined. These three essential views define a paradigm of systems engineering able to structure present-day engineering complexities and risks, and permit project and enterprise control of business achievement and risk exposure. An analysis of the UK MOD acquisition setting for systems engineering, and an Integrated Project Team Leader survey of prevailing system engineering attitudes, experiences, expectations and concerns, set the scene for practice advancements. The first of these is based on a rigorous view of what capability means and how this impacts IPT technical contributions and responsibilities. The effectiveness of the current MOD acquisition cycle is then considered. An alternative, that might better serve the changing nature of investment constraints and effective capability delivery, is presented. Approaches to systems engineering planning are then analysed and a conclusion drawn regarding a planning instrument for IPTs that balances prescription, guidance and didacticism. An assessment of how requirements assist and hinder working with customers and suppliers dissects the intent and content of requirements, including their contrasting technical and commercial purposes. System descriptions, their relationship and their concordance are then considered in a detailed look inside the technical processes, and this includes the principles and methods employed to design architecture. The resolution of current conflicts and confusions over architecture is seen to lie in observance of disciplined systems engineering principles. Finally the systems engineering views of humans inside and outside the system boundary are explored, and the investigation closes with a consideration of the degree to which systems engineering may reasonably address social influences.